Sexual abuse and suicidal behavior: a model constructed from a large community sample of adolescents. - Bergen, H; Martin, G; Richardson, A; Allison, S; Roeger, L (2003)
OBJECTIVE: To investigate relationships between self-reported sexual abuse, depression, hopelessness, and suicidality in a community sample of adolescents. METHOD: In 1995, students (mean age 13 years) from 27 high schools in Australia (n = 2,603) completed a questionnaire including measures of depressive symptoms (Center for Epidemiologic Studies Depression Scale), hopelessness, sexual abuse, and suicidality. Data analysis included logistic regression. RESULTS: Sexual abuse is associated with suicidality, both directly and indirectly through hopelessness and depressive symptoms in the model developed. High suicide risk (behavior exceeding thoughts such as plans and threats, or deliberate self-injury) is strongly correlated with suicide attempts (odds ratio 28.8, 95% CI 16-52, p <.001). Hopelessness is associated with high suicide risk only, whereas depressive symptoms are associated with high suicide risk and attempts. Hopelessness is more strongly associated with sexual abuse in boys than girls. Depressive symptoms are more strongly associated with high suicide risk in girls than boys. Controlling for other variables, sexual abuse is independently associated with suicide attempts in girls but not boys. CONCLUSIONS: Clinical assessment should consider gender differences in relationships between sexual abuse, depressive symptoms, hopelessness, and suicidality. Sexually abused girls may be at increased risk of attempting suicide, independent of other psychopathology.